2002
DOI: 10.1091/mbc.e01-12-0143
|View full text |Cite
|
Sign up to set email alerts
|

The Microtubule-destabilizing Kinesin XKCM1 Regulates Microtubule Dynamic Instability in Cells

Abstract: The dynamic activities of cellular microtubules (MTs) are tightly regulated by a balance between MT-stabilizing and -destabilizing proteins. Studies in Xenopus egg extracts have shown that the major MT destabilizer during interphase and mitosis is the kinesin-related protein XKCM1, which depolymerizes MT ends in an ATP-dependent manner. Herein, we examine the effects of both overexpression and inhibition of XKCM1 on the regulation of MT dynamics in vertebrate somatic cells. We found that XKCM1 is a MT-destabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
133
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(146 citation statements)
references
References 41 publications
12
133
0
1
Order By: Relevance
“…The large increase in astral MTs seen after knockdown of MCAK is consistent with earlier studies showing that MCAK and its orthologues have a dramatic effect on astral MT organization (Walczak et al, 1996;Grill et al, 2001;Maney et al, 2001;Kline-Smith and Walczak, 2002;Goshima and Vale, 2003;Rogers et al, 2004;Srayko et al, 2005). Unfortunately, we were unable to obtain FRAP recovery data on the astral MTs because of the difficulty in obtaining sufficient fluorescence signal to get reliable FRAP curves.…”
Section: What Is the Relationship Between Spindle Mt Dynamics And Orgsupporting
confidence: 88%
See 2 more Smart Citations
“…The large increase in astral MTs seen after knockdown of MCAK is consistent with earlier studies showing that MCAK and its orthologues have a dramatic effect on astral MT organization (Walczak et al, 1996;Grill et al, 2001;Maney et al, 2001;Kline-Smith and Walczak, 2002;Goshima and Vale, 2003;Rogers et al, 2004;Srayko et al, 2005). Unfortunately, we were unable to obtain FRAP recovery data on the astral MTs because of the difficulty in obtaining sufficient fluorescence signal to get reliable FRAP curves.…”
Section: What Is the Relationship Between Spindle Mt Dynamics And Orgsupporting
confidence: 88%
“…Microinjection was carried out as described in Kline-Smith and Walczak (2002), by using either control nonimmune immunoglobulin G (IgG), antiXenopus MCAK (Walczak et al, 1996), or anti-PtK MCAK antibodies, each at needle concentration of 2 mg/ml. Antibodies were stored in antibody dialysis buffer (10 mM HEPES and 100 mM KCl, pH 7.2).…”
Section: Microinjectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitotic centromere-associated kinesin overexpression causes a moderate increase in the frequency of multipolar spindles (Holmfeldt et al, 2004) and monopolar spindles (Kline-Smith and Walczak, 2002), which can contribute to the gain or loss of chromosomes in daughter cells. We reported that overexpression of MCAK leads to the increased migratory and proliferative ability of gastric cancer cells (Nakamura et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Mitotic centromereassociated kinesin destabilises MTs from either end, and this activity and localisation are under the regulation of mitotic kinases (Wordeman et al, 2007). Overexpression of wild-type MCAK induces destabilisation of MTs in both mitotic and interphase cells (Kline-Smith and Walczak, 2002).…”
mentioning
confidence: 99%